Presenilin 1 deficiency impairs Aβ42-to-Aβ40- and angiotensin-converting activities of ACE - Gao, Yuan; Sun, Yang; Islam, Sadequl; Nakamura, Tomohisa; Tomita, Taisuke; Zou, Kun; Michikawa, Makoto (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is associated with amyloid β-protein 1-42 (Aβ42) accumulation in the brain. Aβ42 and Aβ40 are the major two species generated from amyloid precursor protein. We found that angiotensin-converting enzyme (ACE) converts neurotoxic Aβ42 to neuroprotective Aβ40 in an ACE domain– and glycosylation-dependent manner. Presenilin 1 (PS1) mutations account for most of cases of familial AD and lead to an increased Aβ42/Aβ40 ratio. However, the mechanism by which PS1 mutations induce a higher Aβ42/Aβ40 ratio is unclear. Here, we found that ACE purified from PS1-deficient fibroblasts exhibited altered glycosylation and significantly reduced Aβ42-to-Aβ40– and angiotensin-converting activities compared with ACE from wild-type fibroblasts. Overexpression of wild-type PS1 in PS1-deficient fibroblasts restored the Aβ42-to-Aβ40– and angiotensin-converting activities of ACE. Interestingly, PS1 mutants completely restored the angiotensin-converting activity in PS1-deficient fibroblasts, but some PS1 mutants did not restore the Aβ42-to-Aβ40–converting activity. We also found that the glycosylation of ACE in adult mouse brain differed from that of embryonic brain and that the Aβ42-to-Aβ40–converting activity in adult mouse brain was lower than that in embryonic brain. Our findings suggest that PS mutations increase the Aβ42/Aβ40 ratio by reducing the Aβ42-to-Aβ40–converting activity of ACE.